Quality of the information : the application in the winification process in wine production - Ribeiro, Jorge Manuel Ferreira Barbosa (2009)
Knowledge representation techniques as a way to describe the real world, based on mechanical, logical or other means, will be, always, a function of the systems ability to describe the existing world. Knowledge and belief are generally incomplete, contradictory, or error sensitive, being desirable to use formal tools to deal with the problems that arise from the use of incomplete, contradictory, ambiguous, imperfect, or missing information. It is important to evaluate the quality-of-information of the knowledge around the time in order to analyze the best conditions of the universe of the discourse. Based on the vinification process of the wine production this paper analyzes the quality-of-information in the various stages of the process applying Extended Logic Programming as logic mathematical functions.